2021
DOI: 10.3389/fpsyg.2021.634012
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Personality and Locus of Control: Psychological Determinants of Risk Perception and Preventive Behaviors for COVID-19

Abstract: Background: The understanding of factors that shape risk perception is crucial to modulate the perceived threat and, in turn, to promote optimal engagement in preventive actions.Methods: An on-line, cross-sectional, survey was conducted in Italy between May and July 2020 to investigate risk perception for COVID-19 and the adoption of preventive measures. A total of 964 volunteers participated in the study. Possible predictors of risk perception were identified through a hierarchical multiple linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 70 publications
(106 reference statements)
5
20
0
2
Order By: Relevance
“…These results are in accordance with recent studies showing higher psychopathological symptoms resulting from the COVID-19 outbreak among individuals with insecure attachment [48][49][50][51]. Late adolescence represents a critical phase of life marked by instability and feelings of anxiety and depression [78], and a risk window for the onset of psychopathological problems [79][80][81].…”
Section: Main Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in accordance with recent studies showing higher psychopathological symptoms resulting from the COVID-19 outbreak among individuals with insecure attachment [48][49][50][51]. Late adolescence represents a critical phase of life marked by instability and feelings of anxiety and depression [78], and a risk window for the onset of psychopathological problems [79][80][81].…”
Section: Main Findingssupporting
confidence: 92%
“…Conversely, insecure attachment adolescents tend to use maladaptive responses in facing a stressful life event [43,44], showing higher anxiety levels [45], and post-traumatic stress disorder symptoms [46]. Recently, studies have shown that the quality of attachment may also influence individuals' experience of fear during the COVID-19 pandemic and the resulting psychopathological outcomes [44,[47][48][49][50][51]. Specifically, the COVID-19 outbreak can be considered as a stress inducer [52] that may active attachment behavior strategies and the related individual's emotional and behavioral responses used in previous stressful situations [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of measurement issues, the reliability statistic for the locus of control variable was notably low. Locus of control is a crucial component of operationalizing levels of personality, particularly in reference to historical or environmental contexts, and has been assessed in multiple recent COVID-19 studies (Krampe et al, 2021;Lu & Wang, 2021;Tagini et al, 2021), so was retained in analyses despite the low reliability statistic. The influence of locus of control as a defining feature of the agent level of personality, and as a predictor of future outlook in this context, should be interpreted with caution.…”
Section: Limitationsmentioning
confidence: 99%
“…In the absence of a vaccine or treatment for COVID-19, all measures to contain and limit the spread of the infection depend on the behavior of the people. Meanwhile, since the beginning of the pandemic, 2 types of responses to the infection spread have been formed: one part of society perceived the new infection with anxiety and even fear and was actively engaged in preventive protection; the other part, on the contrary, ignored the danger of the disease and protested sharply against all introduced preventive measures (Bump, 2020;Burnett, 2020;Dave et al, 2020;Malone and Bourassa, 2020;Niemi et al, 2021;Tagini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%